Barriers to the Implementation of Electronic Tickets - Mohamad Duengo (Universitas Negeri Gorontalo, 2022)
Abstract:This study aims to determineforms of obstacles in the implementation of electronic ticketing. The method used in this research is empirical or sociological research methodology. This study uses a qualitative approach and sampling using purposive sampling. The results of this study showthat the obstacles in the implementation of the electronic ticket are several things that can affect the ticket not going as expected, including the lack of socialization where this will provide understanding to the public, especially for those road users to be obedient to traffic rules and be aware of function of the electronic ticket applied by law enforcement road traffic department. Furthermore, the second obstacle is that the vehicle plate does not match the owner, meaning that for example a vehicle has changed hands or for example the first party has sold its vehicle to a second party, so that once the second party violates traffic, the electronic ticket will only be sent to the first owner this is because the vehicle that has been purchased has not been reversed by the second party, so this can hinder the passage of the electronic ticket. While the third obstacle in electronic ticketing is the existence of motorbike rentals, where when the motorbike borrower commits a violation, the ticket will only be sent to the motorbike owner from the first party. Therefore, this will make it difficult for law enforcement to impose sanctions on traffic violators through electronic tickets. where when a motorbike borrower commits a violation, a ticket will only be sent to the motorbike owner from the first party. Therefore, this will make it difficult for law enforcement to impose sanctions on traffic violators through electronic tickets. where when a motorbike borrower commits a violation, a ticket will only be sent to the motorbike owner from the first party. Therefore, this will make it difficult for law enforcement to impose sanctions on traffic violators through electronic tickets.